La pérdida en el despojo de tierras y el desplazamiento forzado: ¿una pérdida de objeto o de sujeto? (2021)
This research work aims to understand how the peasants assume or mean the loss of their land in the context of the armed conflict and the acts of dispossession that gave rise to forced displacement. For that, it is investigated what happens when there is a transgression in the relationship of the subject with the object, when it is taken away, when it is stolen? What effects does this generate on the subject? land object change? The foregoing, in light of the testimonies of the victims of land dispossession and forced displacement; as well as the conceptual tools offered by psychoanalysis in relation to the structural elements of the encounter with the real that derives from dispossession, its effects on the subject and the object, and in the relationship of the subject with the land object .